Practical Enzymatic Resolution of Chiral Auxiliaries – Enantiomerically Pure trans-2-Phenylcyclohexanol and trans-2-(α-Cumyl)cyclohexanol - James K. Whitesell; Robert M. Lawrence (CHIMIA)
Commercially available, crude pig liver material (Pig Liver Acetone Powder, PLAP) is demonstrated to be effective for the preparation of enantiomerically pure alcohols that are, in turn, effective chiral auxiliaries for asymmetric induction. Resolution of the title alcohols in large scale is effected by selective enzymatic cleavage of the corresponding acetic acid esters.